Breaking Stereotypes: Male Teachers’ Perspectives on Gender Roles in Early Childhood Education - Syam, A. Sri Mardiyanti; Sulfianita, Sulfianita (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study examined how male in-service and pre-service teachers in Makassar, Indonesia, navigated gender stereotypes in early childhood education (ECE), a profession often viewed as inherently feminine. Using a mixed-methods design, data were collected from ten participants through surveys and semi-structured interviews. Quantitative results showed moderate to high levels of stereotype absorption (M=3.9), understanding (M=4.2), and critical evaluation (M=4.1). Thematic analysis revealed four dominant stereotypes: ECE as a feminized occupational identity, devaluation of professional status, economic disincentive, and institutional neglect. Despite these challenges, participants expressed strong vocational commitment and a desire to redefine masculine roles in nurturing work. The findings emphasized the need for inclusive teacher preparation, gender-responsive policies, and broader public engagement to normalize male participation in ECE. This study offers empirical insight into the lived experiences of male educators and contributes to the pursuit of more gender-equitable and humanistic early education systems.